2020
DOI: 10.1002/cam4.3410
|View full text |Cite
|
Sign up to set email alerts
|

Study and analysis of antitumor resistance mechanism of PD1/PD‐L1 immune checkpoint blocker

Abstract: Immunocheckpoint proteins of tumor infiltrating lymphocytes play an important role in tumor prognosis in the course of tumor clinicopathology. PD‐1 (Programmed cell death protein 1) is an important immunosuppressive molecule. By binding to PD‐L1 (programmed cell death‐ligand 1), it blocks TCR and its costimulus signal transduction, inhibits the activation and proliferation of T cells, depletes the function of effector T cells, and enables tumor cells to achieve immune escape. In recent years, immunocheckpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 243 publications
0
85
0
Order By: Relevance
“…Application of immunotherapy, especially programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) monoclonal antibodies, to a variety of solid tumors (including HCC) represents a major breakthrough in cancer treatment 8 , 9 . However, most patients who have received immunotherapy still experience progression and metastasis 10 . Considering that CSCs are a reservoir for the progression and metastasis of HCC, immunotherapy that targets CSCs may be an exciting research field.…”
Section: Introductionmentioning
confidence: 99%
“…Application of immunotherapy, especially programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) monoclonal antibodies, to a variety of solid tumors (including HCC) represents a major breakthrough in cancer treatment 8 , 9 . However, most patients who have received immunotherapy still experience progression and metastasis 10 . Considering that CSCs are a reservoir for the progression and metastasis of HCC, immunotherapy that targets CSCs may be an exciting research field.…”
Section: Introductionmentioning
confidence: 99%
“…We determined that the 25 factors in the yellow module were most closely related to the content of CD8+ T lymphocytes and were most related to the antigen presentation process and interferon responses. Studies showed that the drug resistance of PD-1 or PD-L1 monoclonal antibody after immunotherapy was closely related to tumor antigen mutation and antigen presentation process [ 26 ]. In addition, the tumor interferon signaling pathway was related to the multigene resistance program that blocks immune checkpoints [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…One cause of it may be related to the heterogeneity of the tumor process and the essence of it is the tumor immune escape. Generally, the drug resistance of ICIs is considered to involve in the interaction of internal and external factors between tumor cells and immune cells within the tumor and the interaction may present a dynamic multilevel change process ( Wang and Wu, 2020 ). The tumor-cell related factors of resistance are considered as intrinsic mechanisms while the immune-cell and micro-environment related factors refer to extrinsic mechanisms of resistance ( Pitt et al, 2016 ).…”
Section: Resistance In Immunotherapymentioning
confidence: 99%
“…A variety of intrinsic and extrinsic factors are involved in tumor cell evasion from immune activation at the genetic, enzymatic, and cellular levels, such as the regulation of TME, intracellular protein mutations, oncogene signal transduction pathways, epigenetic changes, etc. ( Wang and Wu, 2020 ). Whether intrinsic or extrinsic factors, the mechanisms of resistance are concentrated on antigen presentation, cytotoxic T-cell activation and trafficking, as well as the stimulation of the immune-inhibitory axis ( Haibe et al, 2020 ).…”
Section: Resistance In Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation